Research on the Decoupling Effect of China’s Regional Digital Economy Development and Carbon Emissions - Mengke Zhang; Yan Huang; Yuan Bao; Yifan Jin (SHS Web of Conferences, 2023)
The development of digital economy is conducive to empowering technological innovation and optimizing industrial structure, thus reducing the environmental pollution caused by industrial development. However, the development of digital economy also implies an increase in energy demand. Whether its impact on CO2 emissions is the same as or opposite to the Kuznets hypothesis in a “U-shaped” or “N-shaped” relationship, and whether there is a decoupling effect between the two, deserves further study. In this paper, we analyze the non-linear impact of digital economy on carbon emissions through literature research, and the possible decoupling relationship between the two. The decoupling is examined by two measures: velocity decoupling and quantity decoupling. In addition, the inter- and intra-regional variability of digital economy development and carbon emissions is analyzed through the Thiel index. The results of this study add to the empirical techniques and findings on the link between digital economy and carbon emissions, as well as provide theoretical references to support high-quality growth of digital economy and inter-regional cooperation in each region.